Tuberculosis: evaluation of the time between identification of symptoms and beginning of treatment - Lívia Félix de Oliveira; Laura Maria Vidal Nogueira; Ivaneide Leal Ataíde Rodrigues; Pedro Fredemir Palha (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze the time elapsed between the identification of respiratory symptoms and the beginning of tuberculosis treatment, considering the sputum smear microscopy and the RMT. Method: Descriptive, retrospective epidemiological study, carried out in two Health Units, which were the only units that performed diagnosis by sputum smear microscopy and Rapid Molecular Test in the city. Data on respiratory symptoms with a positive result for tuberculosis were used. Analysis of data distribution and variance was performed, with a significance level of 5%. Results: The longest time interval found was "result/beginning of treatment", for both tests, with a median of 3 days. It was found that the patient takes longer to receive the result when performing the Rapid Molecular Test. Conclusion: Patients who had the Rapid Molecular Test waited longer for results when compared to sputum smear microscopy, leading to a reflection on the need for further studies on the operation of health services.